LAW ENFORCEMENT AGAINST JUVENILE DELINQUENCY IN INDONESIA IN RELATION TO THE PURPOSE OF LAW - Sutarjo; Diah Pudjiastuti; Subagyo Sri Utomo; Happy Ferovina Wuntu (Fakultas Hukum Universitas Komputer Indonesia, 2026)
Juvenile delinquency in Indonesia has shown an increasingly serious and complex trend, while the various legal instruments and child protection policies in place have not yet been fully effective in curbing the rate of such deviant behavior. This study specifically aims to analyze the gap between the normative framework of law enforcement against juvenile delinquency—particularly through the Juvenile Criminal Justice System and the principles of restorative justice—and empirical practices in the field, as well as to assess the extent to which responses to juvenile delinquency align with the purposes of law in terms of legal certainty, justice, and utility. Employing a normative and empirical juridical approach, this research examines relevant legislation, policies, and doctrinal views, and integrates them with case data, national statistics, and field findings at the levels of the police, prosecution, courts, and juvenile correctional institutions. The findings reveal that although, at the normative level, the Juvenile Criminal Justice System has shifted the orientation of law enforcement toward rehabilitation and restorative justice through diversion, its implementation remains constrained by the dominance of a legalistic–repressive approach, limited institutional capacity, inadequate rehabilitation facilities, and weak involvement of families and communities in supporting the social reintegration of children. This study offers a comprehensive mapping of the gap between norms and practice and proposes a more integrated response model that positions restorative justice as an instrument for realizing the purposes of law, by strengthening synergy among law enforcement agencies, promoting character education within families and schools, and advancing state policies oriented toward prevention and comprehensive child protection. Kenakalan remaja (juvenile delinquency) di Indonesia menunjukkan kecenderungan yang semakin serius dan kompleks, sementara berbagai instrumen hukum dan kebijakan perlindungan anak belum sepenuhnya mampu menekan laju perilaku menyimpang tersebut. Penelitian ini secara spesifik bertujuan menganalisis kesenjangan antara kerangka normatif penegakan hukum terhadap kenakalan remaja. terutama melalui Sistem Peradilan Pidana Anak dan prinsip keadilan restorative dengan praktik empiris di lapangan, sekaligus menilai sejauh mana penanggulangan kenakalan remaja selaras dengan tujuan hukum berupa kepastian, keadilan, dan kemanfaatan. Dengan menggunakan pendekatan yuridis normatif dan empiris, penelitian ini menelaah peraturan perundang-undangan, kebijakan, dan doktrin terkait, serta memadukannya dengan data kasus, statistik nasional, dan temuan lapangan pada tingkat kepolisian, kejaksaan, pengadilan, serta lembaga pembinaan khusus anak. Hasil penelitian menunjukkan bahwa meskipun secara normatif Sistem Peradilan Pidana Anak telah menggeser orientasi penegakan hukum ke arah pembinaan dan keadilan restoratif melalui diversi, implementasinya masih dibatasi oleh dominasi pendekatan legalistik-represif, keterbatasan kapasitas aparat, minimnya sarana pembinaan, serta lemahnya keterlibatan keluarga dan masyarakat dalam mendukung reintegrasi sosial anak. Penelitian ini menawarkan pemetaan komprehensif atas kesenjangan antara norma dan praktik, sekaligus mengusulkan model penanggulangan yang lebih terpadu dengan menempatkan restorative justice sebagai instrumen aktualisasi tujuan hukum, melalui penguatan sinergi antarlembaga penegak hukum, pendidikan karakter di lingkungan keluarga dan sekolah, serta kebijakan negara yang berorientasi pada pencegahan dan perlindungan komprehensif terhadap anak.